1990
DOI: 10.1037/0278-6133.9.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of rehabilitation in chronic obstructive pulmonary disease: Short-term effects on exercise endurance and health status.

Abstract: Randomly assigned 119 adults with chronic obstructive pulmonary disease to an 8-week comprehensive rehabilitation program or to an 8-week education control program. Comprehensive pulmonary rehabilitation included education, physical and respiratory therapy instruction, psychosocial support, and supervised exercise training, education control included biweekly classroom instruction and discussions on respiratory therapy, medical aspects of lung disease, clinical pharmacology, and diet, but no exercise training.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1
7

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(60 citation statements)
references
References 16 publications
1
51
1
7
Order By: Relevance
“…However, the pattern of these improvements was not entirely consistent, with other studies failing to find improvements in mood (Lennox, Bedell, & Stone, 1990;Segebartt, Nieman, Pover, Arabatzis, & Johnson, 1988), life satisfaction (Blumenthal et al, 1989), or well-being (Toshima et al, 1990). Such discrepancies may well be due to elements of exercise programs, demographics, operational definitions, or a general lack of sensitivity in the measurement technologies employed to assess well-being.…”
Section: Does Physical Activity Influence Psychological Well-being?mentioning
confidence: 46%
See 1 more Smart Citation
“…However, the pattern of these improvements was not entirely consistent, with other studies failing to find improvements in mood (Lennox, Bedell, & Stone, 1990;Segebartt, Nieman, Pover, Arabatzis, & Johnson, 1988), life satisfaction (Blumenthal et al, 1989), or well-being (Toshima et al, 1990). Such discrepancies may well be due to elements of exercise programs, demographics, operational definitions, or a general lack of sensitivity in the measurement technologies employed to assess well-being.…”
Section: Does Physical Activity Influence Psychological Well-being?mentioning
confidence: 46%
“…Indeed, 40% of the studies comprised subjects with a mean age of over 60 years. Of the 38 studies reviewed, 33 employed noninstitutionalized adult samples; the other 5 studies were selected from clinical samples engaged in the exercise component of treatment protocols such as cardiac rehabilitation (Ewart, Taylor, Reese, & Debusk, 1983) or chronic obstructive pulmonary disease (Toshima, Kaplan, & Ries, 1990).…”
Section: Subject Characteristicsmentioning
confidence: 99%
“…However, since no placebocontrolled studies were available, the effective part of the programme was unknown. TOSHIMA et al [18] and more recently, RIES et al [11], showed that a rehabilitation programme, including exercise training, resulted in significantly larger improvements in exercise capacity, symptoms and quality of life than an educational programme alone ( fig. 1).…”
Section: Is Exercise Training Important In Rehabilitation Of Copd Patmentioning
confidence: 99%
“…Indeed, the hyperventilation that induces dyspnoea during exercise [3,4], associated with low aerobic physical fitness due to extensive deconditioning, requires a specific training approach from a ventilatory and metabolic point of view. Despite the substantial training benefits observed in studies of CAL patients [5,6], very few have used the individualized concept. For the last 20 yrs, the intensity of exercise in training prescriptions has been based on criteria such as a percentage of maximal oxygen uptake [7] or maximal heart rate [8][9][10][11], or an empirical level defined by "as tolerated" or "highest level tolerated" [12,13], etc.…”
mentioning
confidence: 99%